2019
DOI: 10.1002/ange.201905198
|View full text |Cite
|
Sign up to set email alerts
|

An Isolable Silicon Analogue of a Ketone that Contains an Unperturbed Si=O Double Bond

Abstract: Despite tremendous efforts to synthesize isolable compounds with an Si = Ob ond, silicon analogues of ketones that contain an unperturbed Si=Obond have remained elusive for more than 100 years.Herein, we report the synthesis of an isolable silicon analogue of ak etone that exhibits at hreecoordinate silicon center and an unperturbed Si = Obond, thus representing the first example of ag enuine silanone.M ost importantly,t his silanone does not require coordination by Lewis bases and acids and/or the introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…isolated a cyclic(amino)(phosphonium‐bora‐ylide)silanone, stabilized by two different π‐donating substituents, an amino group and a more electropositive boron‐based π‐donating phosphonium boraylide functional group [85b] . Later in 2019, Iwamoto and co‐workers synthesized and isolated kinetically stabilized silicon analogue of a ketone with the unperturbed Si=O moiety, which represents the first example of isolable genuine silanone compound [85c] . The oxidation of cyclic dialkylsilylene ( 123 ) with gaseous N 2 O at room temperature led to the formation of silanone ( 124 ) in 100% yield as a white solid (Scheme 46).…”
Section: Heteronuclear Multiple Bondmentioning
confidence: 99%
“…isolated a cyclic(amino)(phosphonium‐bora‐ylide)silanone, stabilized by two different π‐donating substituents, an amino group and a more electropositive boron‐based π‐donating phosphonium boraylide functional group [85b] . Later in 2019, Iwamoto and co‐workers synthesized and isolated kinetically stabilized silicon analogue of a ketone with the unperturbed Si=O moiety, which represents the first example of isolable genuine silanone compound [85c] . The oxidation of cyclic dialkylsilylene ( 123 ) with gaseous N 2 O at room temperature led to the formation of silanone ( 124 ) in 100% yield as a white solid (Scheme 46).…”
Section: Heteronuclear Multiple Bondmentioning
confidence: 99%
“…[6] Even though some recent studies have demonstrated that bulky or/and strongly s-or/and p-donating substituents efficiently stabilize silanones, the synthesis of stable silanones I remains a great challenge and, to date, only a limited number of isolable silanones are available. [7][8][9][10][11][12] A drastic improvement in the stability was achieved by Driesss group, using donor (II) [13] or donor/acceptor (III) [14] systems. [15][16][17][18][19] Thanks to that, several stable and easy-tomanipulate silanone derivatives have been prepared.…”
mentioning
confidence: 99%
“…S8 Si = 360.0. 3 : Mn-Si1 2.268(1), Si1-O1 1.592(2), O1-Mn 2.147(2), N1-Si1 1.791(2), Si1-P 2.310(1), Mn-C (average) 1.820, C-O (average) 1.142, O1-Si1-Mn 64.85(8), Si1-O1-Mn 72.99(8), O1-Mn-Si1 42.16(6), N1-Si1-P 89.90(8), N1-Si1-Mn 133.72( 9), Mn-Si1-P 132.77(4), Si1-Mn-C3 90.58 (10), Si1-Mn-C4 87.26 (11), Si1-Mn-C5 143.61 (11), Si1-Mn-C6 118.19 (13), C3-Mn-C4 174.84( 16), C5-Mn-C6 98.19 (17). (S8 Si(N,P,Mn) = 356.39).…”
mentioning
confidence: 99%
“…Indeed, although the recent studies demonstrated that bulky or/and strongly s-or/and p-donating substituents efficiently stabilize silanones I-V enough to be isolated in the crystalline form, [10][11][12][13][14] most of them remain unstable in solution at room temperature. To the best of our knowledge, only two silanones, such as the chromium-substituted cationic silanone I [10] and cyclic dialkylsilanone V, [14] are stable in solution at RT. However, even silanone V, protected by extremely bulky substituents, dimerizes above 60 8C.…”
mentioning
confidence: 99%
“…This spectral pattern, showing a large transcoupling constant ( 2 J PA-PB = 324.4 Hz) and two small ciscoupling constants ( 2 J PA-PC = 26.0 Hz and 2 J PB-PC = 23.7 Hz), is typical for square planar Rh I complexes, suggesting a classical geometry around the Rh I -center in 2, instead of the unusual distorted tetrahedral geometry observed for silylene 1. [18] The molecular structure of silanone 2 [19] reveals a planar geometry around the three-coordinated silicon atom (S si 8 = 358.398) and a short Si=O bond length [1.540 (3) ] which is longer than those of chromium-substituted silanone I (1.526 ) [10] and of dialkylsilanone V (1.518 ) [14] but is similar to those observed for other p-donor substituted silanones II-IV (1.533-1.543 ). [11][12][13] The N1-Si1 bond length [1.775 3] is almost identical to that of silylene 1 (1.771-1.781 ).…”
mentioning
confidence: 99%